2016
DOI: 10.1021/acs.biomac.5b01019
|View full text |Cite
|
Sign up to set email alerts
|

Release-Modulated Antioxidant Activity of a Composite Curcumin-Chitosan Polymer

Abstract: Curcumin is known to have immense therapeutic potential but is hindered by poor solubility and rapid degradation in solution. To overcome these shortcomings, curcumin has been conjugated to chitosan through a pendant glutaric anhydride linker using amide bond coupling chemistry. The hybrid polymer has been characterized by UV-visible, fluorescence, and infrared spectroscopies as well as zeta potential measurements and SEM imaging. The conjugation reactivity was confirmed through gel permeation chromatography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…This curcumin release at 0 Gy supports previously published results for the release of curcumin from chitosan-curcumin polymer, which concluded that it took 19 days to reach 100% curcumin release via ester-hydrolysis. 27 However, this ester-hydrolysis release prole is not an ideal curcumin release mechanism for situations such as radiation exposure that require rapid drug response aer the harmful stimuli. 27,42 For comparison, the 6 Gy release of 98% curcumin occurred in 30 minutes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This curcumin release at 0 Gy supports previously published results for the release of curcumin from chitosan-curcumin polymer, which concluded that it took 19 days to reach 100% curcumin release via ester-hydrolysis. 27 However, this ester-hydrolysis release prole is not an ideal curcumin release mechanism for situations such as radiation exposure that require rapid drug response aer the harmful stimuli. 27,42 For comparison, the 6 Gy release of 98% curcumin occurred in 30 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…27 However, this ester-hydrolysis release prole is not an ideal curcumin release mechanism for situations such as radiation exposure that require rapid drug response aer the harmful stimuli. 27,42 For comparison, the 6 Gy release of 98% curcumin occurred in 30 minutes. The radiation sensitivity for releasing curcumin from the chitosan-curcumin polymer makes this a unique system for radiation exposure situations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations